当前位置:网站首页>[combinatorics] generating function (commutative property | derivative property | integral property)

[combinatorics] generating function (commutative property | derivative property | integral property)

2022-07-03 17:55:00 Programmer community

List of articles

  • One 、 The commutative property of generating function
  • Two 、 Derivation property of generating function
  • 3、 ... and 、 Integral property of generating function

Reference blog :

  • 【 Combinatorial mathematics 】 Generating function Brief introduction ( Generating function definition | Newton's binomial coefficient | Common generating functions | Related to constants | Related to binomial coefficient | Related to polynomial coefficients )
  • 【 Combinatorial mathematics 】 Generating function ( Linear properties | Product properties )
  • 【 Combinatorial mathematics 】 Generating function ( Shift property )
  • 【 Combinatorial mathematics 】 Generating function ( The nature of summation )

One 、 The commutative property of generating function


Summation property of generating function 1 :

b

n

=

α

n

a

n

b_n = \alpha^n a_n

bn=αnan , be

B

(

x

)

=

A

(

α

x

)

B(x) =A( \alpha x)

B(x)=A(αx)

The sequence

a

n

a_n

an The generating function of is

A

(

x

)

A(x)

A(x) , The sequence

b

n

b_n

bn The generating function of is

B

(

x

)

B(x)

B(x) ,

The sequence

a

n

=

{

a

0

,

a

1

,

a

2

,


}

a_n = \{ a_0 , a_1, a_2 , \cdots \}

an={ a0,a1,a2,} , The sequence

b

n

=

{

α

0

a

0

,

α

1

a

1

,

α

2

a

2

,


}

b_n = \{ \alpha^0a_0 , \alpha^1a_1, \alpha^2a_2 , \cdots \}

bn={ α0a0,α1a1,α2a2,} ;

The sequence

a

n

a_n

an The generating function of

A

(

x

)

=

a

0

x

0

+

a

1

x

+

a

2

x

2

+

A(x) = a_0x^0 + a_1x + a_2x^2 + \cdots

A(x)=a0x0+a1x+a2x2+

The sequence

b

n

b_n

bn The generating function of

B

(

x

)

=

α

0

a

0

x

0

+

α

1

a

1

x

1

+

α

2

a

2

x

2

+

B(x) = \alpha^0a_0x^0 + \alpha^1a_1x^1 + \alpha^2a_2x^2 + \cdots

B(x)=α0a0x0+α1a1x1+α2a2x2+

Method of proof :

stay

b

n

b_n

bn The generating function of

B

(

x

)

B(x)

B(x) in , take

α

0

x

0

\alpha^0x^0

α0x0 As an item , take

α

1

x

1

\alpha^1x^1

α1x1 As an item , take

α

2

x

2

\alpha^2x^2

α2x2 As an item ,

By observing the above items, we can see ,

α

\alpha

α And

x

x

x The power of is the same ,

So you can take

α

x

\alpha x

αx As a variable ,

In this way, you can get

B

(

x

)

=

A

(

α

x

)

B(x) =A( \alpha x)

B(x)=A(αx) The formula ;

Two 、 Derivation property of generating function


Derivation property of generating function :

b

n

=

n

a

n

b_n = n a_n

bn=nan , be

B

(

x

)

=

x

A

(

x

)

B(x) =xA'( x)

B(x)=xA(x)

The sequence

a

n

a_n

an The generating function of is

A

(

x

)

A(x)

A(x) , The sequence

b

n

b_n

bn The generating function of is

B

(

x

)

B(x)

B(x) ,

The sequence

a

n

=

{

a

0

,

a

1

,

a

2

,


,

a

n

,


}

a_n = \{ a_0 , a_1, a_2 , \cdots , a_n , \cdots \}

an={ a0,a1,a2,,an,} , The sequence

b

n

=

{

0

a

0

,

a

1

,

2

a

2

,


,

n

a

n

,


}

b_n = \{ 0a_0 , a_1, 2a_2 , \cdots, na_n ,\cdots \}

bn={ 0a0,a1,2a2,,nan,} ;

The sequence

a

n

a_n

an The generating function of

A

(

x

)

=

a

0

x

0

+

a

1

x

+

a

2

x

2

+

+

a

n

x

n

+

A(x) = a_0x^0 + a_1x + a_2x^2 + \cdots + a_nx^n + \cdots

A(x)=a0x0+a1x+a2x2++anxn+

The sequence

b

n

b_n

bn The generating function of

B

(

x

)

=

0

a

0

x

0

+

1

a

1

x

1

+

2

a

2

x

2

+

+

n

a

n

x

n

+

B(x) = 0a_0x^0 + 1a_1x^1 + 2a_2x^2 + \cdots + na_nx^n + \cdots

B(x)=0a0x0+1a1x1+2a2x2++nanxn+

Prove the above properties :

take The sequence

a

n

a_n

an The generating function of

A

(

x

)

A(x)

A(x) Derivation , Again multiply

x

x

x , You can get

B

(

x

)

B(x)

B(x) ;

A

(

x

)

=

a

0

x

0

+

a

1

x

+

a

2

x

2

+

+

a

n

x

n

+

A(x) = a_0x^0 + a_1x + a_2x^2 + \cdots + a_nx^n + \cdots

A(x)=a0x0+a1x+a2x2++anxn+

Use derivative formula :

(

x

n

)

=

n

x

n

1

(x^n)' = nx^{n-1}

(xn)=nxn1

Reference resources : Derivation - Baidu Encyclopedia

A

(

x

)

=

0

+

a

1

+

2

a

2

x

+

+

n

a

n

x

n

1

+

A'(x) = 0 + a_1 + 2a_2x + \cdots + na_nx^{n-1} + \cdots

A(x)=0+a1+2a2x++nanxn1+

x

A

(

x

)

=

0

+

a

1

x

+

2

a

2

x

2

+

+

n

a

n

x

n

+

=

B

(

x

)

xA'(x) = 0 + a_1x + 2a_2x^2 + \cdots + na_nx^{n} + \cdots = B(x)

xA(x)=0+a1x+2a2x2++nanxn+=B(x)

3、 ... and 、 Integral property of generating function


b

n

=

a

n

n

+

1

b_n = \cfrac{a_n}{n+1}

bn=n+1an , be

B

(

x

)

=

1

x

0

x

A

(

x

)

d

x

B(x) =\cfrac{1}{x} \int^{x}_{0} A( x)dx

B(x)=x10xA(x)dx

The above properties are hard to remember , Generate functions from known , Unknown generating functions can be derived , You can deduce when using ;

原网站

版权声明
本文为[Programmer community]所创,转载请带上原文链接,感谢
https://yzsam.com/2022/02/202202150323588467.html